Dalil Hukum Wali, Saksi dan Usia Menikah - Fatimah Fatimah; Mhd. Amar Adly; Heri Firmansyah (Student Research Journal, 2025)
The position of the guardian in the marriage contract is a very important aspect in determining the validity of a marriage contract between a male and female couple. What is meant by guardian in marriage is someone who acts on behalf of the bride in a marriage contract. Indeed, there is not a single verse in the Koran that clearly (explicitly) explains the existence of a guardian in a marriage contract. To realize this goal, there are the pillars of marriage, namely the groom, the bride, the guardian, two witnesses and the consent qobul. There is a very striking difference among the scholars of the four two pillars of marriage, namely: guardian and two witnesses. Some of the four school of thought scholars include it as a pillar and some do not include it as a pillar; some say it is a valid requirement and there are also those who say it is only a complement. Departing from this background, there is a question, what is the position of guardians and witnesses in marriage according to the four schools of thought? Answering this question, the number of ulama argued that guardians and witnesses are one of the pillars of marriage and are a benchmark for the validity of a marriage. Hanafiyyah ulama said that guardians are only complements. The Malikiyyah ulama place witnesses under Sunnah law, but require the presence of a guardian when having intimate relations. Then the age limit for marriage in Islam was analyzed by sectarian scholars. To find out what the age limit for marriage is in Islam, it was then analyzed by Islamic school scholars. Islam itself does not limit the ideal age for marriage. However, in general, what is commonly known is that they are baliq, have good sense, are able to distinguish between good and bad so that they can give consent to marriage, when the time has come for someone to get married (buluq an-nikah), with the word "rusyd". The fuqaha have different opinions regarding the age limit for marriage, where the Shafi'i and Hanbali schools argue that the ideal age for marriage is 15 years, while Abu Hanifa believes that the age of maturity comes at 19 years for women and 17 years for men, others Likewise, Imam Malik believes that the ideal age of maturity is 18 years for both men and women.